Post-Operative Monitoring of Intestinal Tissue Oxygenation Using an Implantable Microfabricated Oxygen Sensor - Jamie R. K. Marland; Mark E. Gray; David J. Argyle; Ian Underwood; Alan F. Murray; Mark A. Potter (Micromachines, 2021)
Anastomotic leakage (AL) is a common and dangerous post-operative complication following intestinal resection, causing substantial morbidity and mortality. Ischaemia in the tissue surrounding the anastomosis is a major risk-factor for AL development. Continuous tissue oxygenation monitoring during the post-operative recovery period would provide early and accurate early identification of AL risk. We describe the construction and testing of a miniature implantable electrochemical oxygen sensor that addresses this need. It consisted of an array of platinum microelectrodes, microfabricated on a silicon substrate, with a poly(2-hydroxyethyl methacrylate) hydrogel membrane to protect the sensor surface. The sensor was encapsulated in a biocompatible package with a wired connection to external instrumentation. It gave a sensitive and highly linear response to variations in oxygen partial pressure in vitro, although over time its sensitivity was partially decreased by protein biofouling. Using a pre-clinical in vivo pig model, acute intestinal ischaemia was robustly and accurately detected by the sensor. Graded changes in tissue oxygenation were also measurable, with relative differences detected more accurately than absolute differences. Finally, we demonstrated its suitability for continuous monitoring of tissue oxygenation at a colorectal anastomosis over a period of at least 45 h. This study provides evidence to support the development and use of implantable electrochemical oxygen sensors for post-operative monitoring of anastomosis oxygenation.